Sails.js in action - McNeil, Mike (Michael Ryan); Nathan, Irl (Manning Publications Co., 2017)
Sails.js in Action is a comprehensive guide to building enterprise-capable web applications using Node and Sails. Written by the creators of the Sails.js framework, this book carefully introduces each concept, technique, and tool with real-world examples and crystal clear explanations. About the Technology Sails makes professional web development a breeze. This instantly familiar MVC framework automatically handles the tedious application boilerplate, so you can concentrate on developing features and creating business value. You get powerful tools for rapid API development, task automation, an ORM, and easy integration with any web, mobile, or IoT frontend. And because you're using Node.js, it's JavaScript all the way down. About the Book Sails.js in Action is a comprehensive guide on how to build enterprise-capable web applications. Written by the creators of Sails.js, this book introduces each concept and technique with real-world examples and thorough explanations. As you read, you'll learn to build the backend of a typical web application while you explore real-time programming with WebSockets, security fundamentals, and best practices for building Sails/Node.js apps. What's Inside Creating the backend for a web, mobile, or IoT app Real-time programming with WebSockets User management, authentication, and password recovery Using Sails to autogenerate REST APIs Custom backend development and third-party API integrations About the Reader Readers should be comfortable with JavaScript and frontend web development. About the Authors Mike McNeil is the creator of Sails.js. Irl Nathan is the producer of sailsCasts, a series focused on using Sails.